A positive regulatory gene, THI3, is required for thiamine metabolism in Saccharomyces cerevisiae - Nishimura, H. (Kyoto Prefectural University of Medicine, Kamigyo-ku, Kyoto, Japan); Kawasaki, Y; Kaneko, Y; Nosaka, K; Iwashima, A (Journal of Bacteriology, 1992)
We have isolated a thiamine auxotrophic mutant carrying a recessive mutation which lacks the positive regulatory gene, THI3, which differs in the regulation of thiamine transport from the THI2 (PHO6) gene described previously (Y. Kawasaki, K. Nosaka, Y. Kaneko, H. Nishimura, and A. Iwashima, J. Bacteriol. 172:6145-6147, 1990) for expression of thiamine metabolism in Saccharomyces cerevisiae. The mutant (thi3) had a markedly reduced thiamine transport system as well as reduced activity of thiamine-repressible acid phosphatase and of several enzymes for thiamine synthesis from 2-methyl-4-amino-5-hydroxymethylpyrimidine and 4-methyl-5-beta-hydroxyethylthiazole. These results suggest that thiamine metabolism in S. cerevisiae is subject to two positive regulatory genes, THI2 (PHO6) and THI3. We have also isolated a hybrid plasmid, pTTR1, containing a 6.2-kb DNA fragment from an S. cerevisiae genomic library which complements thiamine auxotrophy in the thi3 mutant. This gene was localized on a 3.0-kb ClaI-BglII fragment in the subclone pTRR5. Complementation of the activities for thiamine metabolism in the thi3 mutant transformed by some plasmids with the THI3 gene was also examined